2017
DOI: 10.3389/fnut.2017.00013
|View full text |Cite|
|
Sign up to set email alerts
|

Current Concepts and Unresolved Questions in Dietary Protein Requirements and Supplements in Adults

Abstract: Protein needs for otherwise healthy individuals older than 19 years are defined by the recommended dietary allowance (RDA) at 0.80 g protein/kg/day. There is no recommendation in the current RDA for subpopulations of older adults or people in various pathological situations. Despite the lack of a separate recommendation, there exists a growing body of evidence that is strongly suggestive of an increased need and/or benefit for protein in older persons. That is, intakes beyond the RDA are, in older persons, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 120 publications
(187 reference statements)
1
89
0
Order By: Relevance
“…It is accepted that when reducing energy intake, macronutrients should not be cut evenly, as maintaining a high-protein intake will be essential to attenuate loss in lean muscle mass. For instance, leucine consumption, which is a key and critical amino acid for stimulating the cell signaling pathways that control muscle protein synthesis, should be emphasized in the protein sources consumed [36].…”
Section: Detraining Effects In Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accepted that when reducing energy intake, macronutrients should not be cut evenly, as maintaining a high-protein intake will be essential to attenuate loss in lean muscle mass. For instance, leucine consumption, which is a key and critical amino acid for stimulating the cell signaling pathways that control muscle protein synthesis, should be emphasized in the protein sources consumed [36].…”
Section: Detraining Effects In Isolationmentioning
confidence: 99%
“…Focus on neuromuscular plyometrics (i.e., vertical and horizontal jumping) and eccentric training (i.e., elastic bands), to maintain some key adaptations related to the stretch-shortening cycle, strength and power performance. Adaptations of the stabilizer muscles as an indispensable element and facilitator of the efficient sensorimotor action of any act is also extremely important [46,47]; -Educate the athlete about nutrition, supplementation (especially Vitamin D, zinc and proteins) and hydration in isolation conditions, and about strategies to control body mass and body composition [5,36,48,49]. It is important to consume food to fight off viral infections, thus advising against lower carbohydrate/intermittent fasting approaches is likely important [50]; -Organize mental fatigue monitoring and mental training (mental self-help techniques and/or the support of a psychologist by telecommunication) [51]; -Provide adequate methods of recovery (supplementation, sleep, breathing and meditation exercises, self-massage, myofascial relaxation, stretching, low back heat, etc.)…”
Section: Window Of Opportunity During the Isolationmentioning
confidence: 99%
“…There are a number of long-standing claims that a high protein diet, as advocated here for track and field athletes during weight loss, is detrimental for athlete health (Lowery & Devia, 2009;Martin et al, 2005;Metges & Barth, 2000). However, at present, there is no scientific evidence to substantiate the claims that protein will enhance risk of adverse renal health, particularly within athletic populations (Phillips, 2017;Phillips et al, 2016;Van Elswyk et al, 2018). Moreover, as opposed to what is often touted as a negative effect of high protein in stimulating adverse outcomes for bone, a recent meta-analysis from the U.S. National Osteoporosis Foundation concluded that protein is actually a bone supportive nutrient (Shams-White et al, 2017) particularly when athletes are consuming adequate calcium and vitamin D. In short, track and field athletes who consume a high protein diet during weight loss are not placing themselves at increased risk of kidney problems or poor bone health.…”
Section: High Protein Diets For Health and Performance In Track And Fmentioning
confidence: 99%
“…Data from several observational and experimental studies gathered in recent review papers have demonstrated that current protein RDA is insufficient to the meet minimum requirements to counteract skeletal muscle loss with aging and promote hypertrophy of this body compartment in healthy older adults (Bauer et al 2013;Deutz et al 2014;Phillips 2017a). Therefore, current protein recommendations for older adults is not sufficient to prevent sarcopenia, which precludes DRIs' objective of maintaining and promoting health, as well as preventing chronic diseases (Institute of Medicine 2005).…”
Section: Dietary Proteinmentioning
confidence: 99%
“…Several recent reviews have also criticized current protein recommendation for older adults and proposed adjustments for sarcopenia prevention (Paddon-Jones et al 2008;Gaffney-Stomberg et al 2009;Paddon-Jones and Leidy 2014;Deer and Volpi 2015;Nowson and O'Connell 2015;Baum et al 2016;Courtney-Martin et al 2016;Landi et al 2016;Murphy et al 2016;Phillips et al 2016;Shad et al 2016;Naseeb and Volpe 2017;Phillips 2017a). A summary of protein intake recommendations for healthy older adults proposed by recent review articles is shown in supplementary Table S1 1 .…”
Section: Quantitymentioning
confidence: 99%